Synthesis of 2-(t-Butyl)dimethyl-silyloxy-2-cyclopropyl- 1-ethyl-triphenylphosphonium iodide and Its Crystal Structure - Wang1, Wei; Shen2, Yong-Miao (Asian Journal of Chemistry, 2011)
Compound of 2-( t-butyl)dimethyl-silyloxy-2-cyclopropyl-1-ethyl-triphenylphosphonium iodide (C29H38IOPSi) has been synthesized through1/n with unit cell parameters:a = 90º, b = 95.5280(10) º, g = 90º, v = 3009.56(7) Å3, z = 4, Dc = 1.299 Mg/m3,-1. The final R and wR are 0.0444 and 0.1178, respectively for 5312 observed reflectionss(I). five steps and the structure was determined by X-ray diffraction. The crystal is monoclinic, space group P2 a = 13.6074(2) Å, b = 13.0416(2) Å, c = 17.0381(2) Å. Mr = 588.55, F(000) = 1208 and μ = 1.175 mm with I > 2